PENGARUH GAYA KEPEMIMPINAN DAN KOMITMEN ORGANISASI TERHADAP DISIPLIN KERJA DENGAN KEPUASAN KERJA SEBAGAI VARIABEL INTERVENING - Setiawan, Edi; Mardalis, Ahmad (Jurnal Manajemen Dayasaing, 2015)
The purpose of this study to analyze the factors - factors that can affect employeesatisfaction and working discipline in PT. PLN (Persero) AREA Surakarta. The researchmodel that will be used in this research is a model of a tiered structure. The results ofthis study indicate that the style of leadership is not a positive influence on the discipline of work, organizational commitment positively affects work discipline, organizational commitment has positive effect on job satisfaction. Variability construction work discipline can be explained by the variability of the construct of leadership styles, organizational commitment, and job satisfaction. Model influence leadership style and organizational commitment to job satisfaction produce R-square values show moderate models, it means that the job satisfaction construct variability can be explained by the variability of the construct of leadership style and organizational commitment.